Association between Polymorphisms in DNA Base Excision Repair Genes XRCC1, APE1, and ADPRT and Differentiated Thyroid Carcinoma - Chiang, Feng-Yu; Wu, Che-Wei; Hsiao, Pi-Jung; Kuo, Wen-Rei; Lee, Ka-Wo; Lin, Jen-Chih; Liao, Yi-Chu; Juo, Suh-Hang Hank (Clinical cancer research, 2008)
Purpose: DNA BER pathway is related with carcinogenesis. We hypothesized that functional polymorphisms of three BER genes, XRCC1, apurinic/apyrimidinic endonuclease ( APE1 ), and ADPRT , confer risks for DTC and its progression. Experimental Design: Five common nonsynonymous single nucleotide polymorphisms ( Arg194Trp, Arg280His, and Arg399Gln for XRCC1 ; Asp148Glu for APE1 ; and Val762Ala for ADPRT ) were genotyped in Chinese DTC cases and controls. Results: The XRCC1-194Trp/Trp genotype showed a significantly increased risk for DTC (odds ratio, 1.85; 95% confidence interval, 1.11-3.07; P = 0.018). Subset analysis based on regional LN metastasis showed that the genetic effect came primarily from the subjects with LN metastasis (odds ratio, 4.54; 95% confidence interval, 2.11-9.79; P = 0.0001), but no significant association for subjects without LN metastasis. The other four single nucleotide polymorphisms did not show significant results. Haplotype analysis of XRCC1 polymorphisms yielded a significant result ( P = 0.004), especially in the subjects with LN metastasis ( P = 0.0002). Moreover, we found that XRCC1-194Trp and ADPRT-762Ala variants collectively contributed to an increased risk of the disease and LN metastasis, with the combined variant homozygotes exhibiting the highest 3.18-fold risk for DTC ( P = 0.046) and 9.25-fold risk for DTC with LN metastasis ( P = 0.004). Conclusions: The XRCC1 polymorphisms, especially the 194Trp allele, may have an effect on DTC development and progression. This variant can interact with ADPRT-762Ala variant to further substantially increase susceptibility to the disease and regional LN metastasis. Identifying these risk genetic markers could provide more insight into the DTC pathogenesis and may also provide information to develop better prevention and therapeutic strategies.